Studies of jet mass in dijet and W/Z + jet events - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Aguilo, E.; Bergauer, T.; Dragicevic, M.; Erö, J.; Fabjan, C.; Friedl, M.; Frühwirth, R.; et al. (My University, 2013)
Invariant mass spectra for jets reconstructed using the anti-k T and CambridgeAachen algorithms are studied for different jet grooming techniques in data corresponding to an integrated luminosity of 5 fb-1, recorded with the CMS detector in proton-proton collisions at the LHC at a center-of-mass energy of 7 TeV. Leading-order QCD predictions for inclusive dijet and W/Z+jet production combined with parton-shower Monte Carlo models are found to agree overall with the data, and the agreement improves with the implementation of jet grooming methods used to distinguish merged jets of large transverse momentum from softer QCD gluon radiation. © 2013 CERN for the benefit of the CMS collaboration.
Keywords: Hadron-Hadron Scattering